Strategi Pengembangan Koperasi Jasa Keuangan Syariah dalam Pembiayaan Usaha Mikro di Kecamatan Tanjungsari, Sumedang - - Pristiyanto; Mochamad Hasjim Bintoro; Soewarno Tjokro Soekarto (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2013)
KJKS as Islamic microfinance institution have a strategic role in the expansion of employment and reduce poverty. KJKS have a role as agent of asset distribution for the economic empowerment of the community, through Baitul Maal activities which is serve as a social institution and Baitul Tamwil which is serve as business institutions with Islamic patterns. The aimed of the study were (1) Identify the KJKS aspects, (2) Identify internal and and external factors that may indicate the position of cooperatives and opportunities, (3) Arrange appropriate formulation and alternative strategic for development of KJKS. Data were collected with primary and secondary data collection through library, field observation, questionnaires, worksheets and interview skills approach (administrators/managers and experts).  Techniques and data processing using descriptive analysis both normative (according to the rules of sharia and legislation in force), qualitative (describing the profile, products and processes as well as business activities KJKS describe IFE matrix, EFE, IE, SWOT and QSPM), and quantitative (do the calculation above tabulation health assessment and weighting of the IFE, EFE, and IE). Data processing is done using Microsoft Office Excel 2007 and SPSS ver. 15.0 for Windows. Data showed from scoring through IFE matrix (3.14) and EFE (2.92) and grouping strategies using IE matrix that KJKS Mardlotillah BMT are at the Development and Expansion. The strategy is designed to achieve capital growth conditions, asset and financing for micro distribution cooperative members. Development Strategy KJKS BMT Mardlotillah generated SWOT matrix and QSP obtained suggested five strategic priorities are: (1) Improved quality of service and sharia business management, (2) Increasing cooperatives imaging through improved internal oversight and accountability of financial statements and (3) Increase the quality of human resources that are reliable and robust, (4) Establish a good relationship/partnership with the financial institutions, and 5) Optimization services and coaching/mentoring business member loyalty to motivate and saving members interests.